C-Terminal Extended Hexapeptides as Potent Inhibitors of the NS2B-NS3 Protease of the ZIKA Virus - Pant, Suyash; Jena, Nihar R. (Frontiers in Medicine, 2022)
The Zika virus (ZIKV) protease is an attractive drug target for the design of novel inhibitors to control viral infection. As the protease substrate-binding site contains acidic residues, inhibitors with basic residues can be beneficial for the inhibition of protease activities. Molecular dynamics (MD) simulation and molecular mechanics with generalized Born and surface area solvation (MM/GBSA) techniques are employed herein to design potent peptide inhibitors and to understand the nature of the basic residues that can potentially stabilize the acidic residues of the protease substrate-binding site. It is found that the inclusion of K, R, and K at P1, P2, and P3 positions respectively, and Y at the P4 position (YKRK) would generate a highly stable tetrapeptide-protease complex with a Gbind of ~-80 kcal/mol. We have also shown that the C-terminal extension of this and the second most stable tetrapeptide (YRRR) with small polar residues, such as S and T would generate even more stable hexapeptide-protease complexes. The modes of interactions of these inhibitors are discussed in detail, which is in agreement with earlier experimental studies. Thus, this study is expected to aid in the design of novel antiviral drugs against the ZIKV.